PENINGKATAN KEMAMPUAN BADAN AMIL MENGGUNAKAN FITUR E-ZAKAT SEBAGAI MEDIA PENYALURAN KEPADA MUSTAHIQ - Muhamad Awiet Wiedanto Prasetyo; Rizky Bangkit Bachtiar; Indika Manggala Putra; Laely Candra Arviana (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
The distribution of zakat fitrah coincides on the 30th of Ramadhan Hijriyah as in Kedunggede Village. There are prolems in the process of zakat distribution, the results of the reports from each hamlet must be known and singed by the committee chairman of the village administration and then determine the nominal money and weight of rice distributed. The solution offered is to implement an application that has been made by adjusting the needs partners, with the E-Zakat feature. The flow service method starts from presenting the existing infrastructure in Kedunggede Village regarding the use of information technology the presenting the use of the E-Zakat feature. The conclusion of this Amikom Mitra Masyarakat activity is that when the village amil zakat practice the E-Zakat feature it gets a good response and the amil zakat provides a satisfactory assessment because it can provide realtime information so that the time efficiency is felt.